PENGARUH KOMITMEN ORGANISASI, KEPUASAN KERJA, DAN KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI BIRO ADMINISTRASI PEMERINTAHAN UMUM PROVINSI RIAU - Zuhrah Nadima Ulfah Damri; Marzolina '; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the influence of organizational commitment, job satisfaction, and leadership on discipline employees working in Bureau of the General Administration of Riau Province. Population in this study were all employees of the Bureau of the General Administration of Riau province which numbered 60 people, the method of sampling is using saturation sampling methods and data analysis using multiple linear regression were processed with SPSS version 18.0. From the regression testing showed that organizational commitment, job satisfaction, and leadership do effect to discipline employees working in the Bureau of the General Administration of Riau Province. The contribution of the influence of the independent variables (Organizational Commitment, Job Satisfaction and Leadership) on the dependent variable (Work Discipline) amounted to 81.3%. From the research, the author propose agencies should have a deeper socialization on the vision, mission, values, and regulations that apply to the company so that employees are able to understand their duties and responsibilities so that the implementation can be run properly in accordance with the direction and objectives of the agency. With this socialization is expected to lead to a commitment within selalalu employees so that employees want to work with really - really and hard work in achieving agency objectives.Keyword : Organizational Commitment, Job Satisfaction, Leadership And Discipline Employees.